Existence of Estoppel Doctrines in Common Law Contracts: Challenges and Opportunities for Civil Law-Based Lawyers - Elisabeth, Novita Sartika (Talenta Publisher, Universitas Sumatera Utara, 2023)
A basic concept of contract is an object of law that is often defined as an agreement made by parties to perform duties and obligations and receive rights in return. The legal positions of parties involved in a contract are governed by contract law that is complex. It covers principles, doctrines, rights, obligations, and access to remedy regarding any breach of the contract. The complexities of the contract law are further inevitably impacted by the system of the law within a country. The principles, regulations, and legal concepts in civil law countries generally rely heavily on written forms. In contrast, common law countries based the law on precedent cases or the developments of court decisions. This fundamental difference potentially causes either challenges or opportunities for the lawyers practising outside their jurisdiction, as the application of the concepts and doctrines used are different. This paper will discuss a distinguished difference in a doctrine of contract law adopted by the common law system like Australia, which is called Estoppel, that might remain less applied in civil law countries like Indonesia.